SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BANTUAN RS-RUTILAHU DENGAN METODE TOPSIS PADA DESA KOTABATU CIOMAS KABUPATEN BOGOR - Enok Tuti Alawiah; Dwi Andini Putri (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
Non-Eligible Houses for Social Rehabilitation (RS-RUTILAHU) is a program of assistance from the social ministry to fulfill the needs of decent homes as an element of social welfare. Assistance is channeled to the people who need it according to the eligibility criteria. This research was carried out so that the RUTILAHU Hospital assistance program in Kotabatu Village, Ciomas District, Bogor Regency could be received on target. The research method used is the method TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). TOPSIS is a multicriteria decision-making method based on the concept that the best alternative not only has the shortest distance from a positive ideal solution but also has the longest distance from a negative ideal solution. The Decision Support System can be used to help village governments to determine the right to get RS-RUTILAHU program on target. The results of the study can be used as a reference so that the provision of RS-RUTILAHU assistance programs can be provided to eligible residents according to the eligibility criteria.